Financial Security of the Insurance Market in Ukraine (Economics and region, 2023)
The article addresses the pressing issue of the functioning and development of the insurance market in Ukraine, which requires fundamental changes. The essence of the insurance market as an economic category and one of the most vital segments of the economy is examined. Attention is paid to the theoretical foundations of its operation, including its role in the economic system of the state. This role involves safeguarding the population against unforeseen factors, risk management, savings allocation, facilitating capital market growth, and more. The paper investigates the structure of the insurance services market, the principles on which its activities are based, and the regulatory framework governing it. In particular, a comparison is made between the Ukrainian Insurance Laws of 1996 and 2021, highlighting the main changes and innovations. The article provides a classification of the main types of insurance, presents characteristics of key indicators that demonstrate the level and prospects of the insurance market's development, along with its functions and features. The analysis of the Ukrainian insurance market's activity has revealed the main trend of its development and identified the contemporary conditions in which it operates, including the COVID-19 pandemic, the state of war, and economic-social crises. It is established that the domestic insurance market is a promising segment, albeit currently characterized by a low level of development. The major indicators characterizing the performance of the Ukrainian insurance services market have been analyzed, along with their dynamics from 2016 to 2021. The research results are presented in tabular and graphical form. The comprehensive analysis of financial security indicators of the Ukrainian insurance market for the period from 2001 to 2020 was also conducted, leading to the conclusion of its low level of financial security. In conclusion, the justification for the systematization of measures and directions to support the development of the insurance market in conditions of a state of war and its subsequent stimulation in the post-war period was provided. These measures are expected to have a positive impact on Ukraine's economic system and contribute to the increase in the level of financial security, both for individual segments, particularly the insurance sector, and for the state as a whole. Key factors promoting the accelerated development of the insurance market were identified, and recommendations were provided for its post-war recovery and growth. Lastly, the importance of an effective financial security management system for the insurance market was emphasized.
Keywords: insurance market; financial security of the insurance market; indicators; threats; state of war